2020
DOI: 10.1093/ibd/izaa188
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease–Associated Changes in the Gut: Focus on Kazan Patients

Abstract: Background Several studies have highlighted the role of host–microbiome interactions in the pathogenesis of inflammatory bowel disease (IBD), resulting in an increasing amount of data mainly focusing on Western patients. Because of the increasing prevalence of IBD in newly industrialized countries such as those in Asia, the Middle East, and South America, there is mounting interest in elucidating the gut microbiota of these populations. We present a comprehensive analysis of several IBD-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…The fecal pellets were collected directly from mice at 45 day after birth and stored at − 80 °C prior to SCFA determination. SCFAs were quantified in feces samples (1 g) by gas–liquid chromatographic analysis (GLC; Agilent, USA) [ 35 ]. Commercial acetic, propionic and butyric acids were used as standards [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fecal pellets were collected directly from mice at 45 day after birth and stored at − 80 °C prior to SCFA determination. SCFAs were quantified in feces samples (1 g) by gas–liquid chromatographic analysis (GLC; Agilent, USA) [ 35 ]. Commercial acetic, propionic and butyric acids were used as standards [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…SCFAs were quantified in feces samples (1 g) by gas–liquid chromatographic analysis (GLC; Agilent, USA) [ 35 ]. Commercial acetic, propionic and butyric acids were used as standards [ 35 ]. The overall level of SCFAs is presented as the sum of all concentrations of acids and isoacids in µg/g.…”
Section: Methodsmentioning
confidence: 99%
“…Analogous to studies that showed little effect of the F/B ratio on obesity, a decreased F/B ratio was also not observed in all IBD cases. A fecal microbial analysis of IBD patients from Kazan revealed decreased abundancies of Bacteroidetes, Firmicutes, and Verrucomicrobia, while the abundancies of Proteobacteria, Actinobacteria, and Fusobacteria were increased [79]. In 48 UC patients, the Bacteroides bacterial copy number in fecal samples was less than 10% of that in healthy individuals, and the Clostridium subcluster XIVab (Firmicutes) was also significantly lower [80].…”
Section: The Role Of a Decreased F/b Ratio In Ibdmentioning
confidence: 96%
“…SCFAs can be used as energy sources and critical small molecules to regulate host gene expression and inflammation [ 22 ]. Moreover, an increase in the abundance of Actinobacteria has usually been associated with diseases, such as inflammatory bowel disease [ 23 ], mental disorders [ 24 , 25 ], type 2 diabetes [ 26 ], and epilepsy [ 27 ]. Cyanobacteria play a role in neurodegenerative diseases by producing a variety of toxic metabolites, such as β-methylamino-1-alanine, 2,4-aminobutyric acid, and N-2-aminoethylglycine [ 28 ].…”
Section: Discussionmentioning
confidence: 99%